An experimental and analytical investigation into age-dependent strength of fly ash mortar at elevated temperature. (20th October 2019) - Rais, M.S.; Shariq, M.; Masood, A.; Umar, A.; Alam, M.M.
Highlights: Studied the effect of high temperature on age-dependent strength of fly ash mortar. Fresh, age-dependent, microstructure properties were investigated up to 500 °C. Fly ash mortar after exposure to elevated temperature showed better performance. Formation and growth of micro-cracks is larger in OPC than fly ash mortar at 500 °C. A model is proposed to predict fly ash mortar strength at elevated temperature. Model is useful in concrete construction, contributes in sustainable development. Abstract: The impact of high temperature on the fresh, age-dependent strength and microstructure properties of low and high content fly ash mortars has been examined in the current investigation. Cement was replaced with fly ash by 0%, 10%, 25%, 40% and 50% on an equal weight basis. The mortar specimens were prepared using blended cement (i.e. cement + fly ash): fine aggregate proportion of 1:3 and water to binder proportion ranging from 0.415 to 0.44 and cured under water for the ages varying from 7 to 90 days. Then, the specimens were dried and then exposed to one heating-cooling cycle of high temperatures starting from 100 °C to 500 °C at an interval of 100 °C for 3 h. The residual strength of blended mortar in compression was measured and compared with plain mortar strength. The morphological characteristics using scanning electron microscopy has also been observed. The blended mortar containing 10% fly ash when exposed up to 500 °C temperatures gives better performance. The microstructure analysis showed that plain mortar at 500 °C is having larger micro-cracks formation and growth than blended mortar containing 10% fly ash. A model is proposed for the prediction of age-dependent compressive strength of blended mortar after heating at high temperature and found good agreement with experiments. The proposed model will be useful in concrete construction and also contribute to sustainable development. Using the proposed model, the age-dependent strength of fly ash mortar at elevated temperature can be predicted, when 28 days strength of plain mortar at ambient temperature is available.